Considering disproportionality in school discipline: promising practices and policy. Issue 1 (2nd January 2022) - Scott, Terrance M.; McIntosh, Kent
ABSTRACT: Racial disproportionality in school discipline has always been a threat to equitable education in the United States. This introduction to the special issue provides an overview of the topic and describes the articles and their potential contribution to improving equity in school discipline.